Articulating performance expectations for scholarship at an Australian regional university. Issue 1 (2nd January 2016) - Crookes, Patrick A.; Smith, Kylie M.; Else, Fabienne C.; Crookes, Ellie
Abstract : With an academic workforce undergoing transformation, it is vital that universities rethink how they define and value scholarship through their processes for academic promotion. A key part of this rethink is to review and refine existing documentation about promotion to reflect changing conceptions of scholarly work, in a way that enables scholars from non-traditional academic pathways to be valued equally through the promotion process with their more traditional counterparts. This process of reviewing scholarship was the aim of a promotions review project which began at the University of Wollongong in 2011 and concluded with the production of an Academic Performance Framework (APF). This framework outlines a new way of articulating performance expectations in order to recognise scholarship more broadly, as well as to emphasise more clearly the imperative for academics to be able to articulate evidence of the impact of their work.